The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5021/ad.2011.23.4.529
|View full text |Cite
|
Sign up to set email alerts
|

CD20 Positive T Cell Lymphoma Involvement of Skin

Abstract: CD20 positive T cell lymphoma is a rare condition that is associated with the coexpressions of CD20 and T cell markers, such as, CD3, CD5, or UCHL-1. Positivity for CD20 in this tumor represents an aberrant immunophenotype, but the presence of monoclonal T cell receptor (TCR) gene rearrangements and negativity for immunoglobulin heavy chain gene rearrangement indicate that this tumor is a T cell lymphoma. The majority of cases of CD20 positive T cell lymphoma have been reported as immature peripheral T cell ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Among the markers to determine B- and T-cell lineages, CD20 and CD3 are the most commonly used. T-cell lymphomas with aberrant expression of the B-cell marker CD20 or B-cell lymphomas with aberrant expression of T-cell associated antigens such as CD5, CD43, CD7, CD2, CD4, and CD8 have been reported [1-5]. However, cases of B-cell lymphoma with CD3 co-expression are extremely rare [6, 7].…”
mentioning
confidence: 99%
“…Among the markers to determine B- and T-cell lineages, CD20 and CD3 are the most commonly used. T-cell lymphomas with aberrant expression of the B-cell marker CD20 or B-cell lymphomas with aberrant expression of T-cell associated antigens such as CD5, CD43, CD7, CD2, CD4, and CD8 have been reported [1-5]. However, cases of B-cell lymphoma with CD3 co-expression are extremely rare [6, 7].…”
mentioning
confidence: 99%
“…Of these 11 cases, 6 were PTL-U, 4 were MF, and 1 case was of small/medium CD4+ T-cell lymphoma. 108,114 (Table 4) In addition, Vergier et al 103 in their series of MF cases transformed to large cell lymphoma found CD20-positive reactive B-cells in 18 of 40 cases, many of which also expressed CD20 antigen on transformed large neoplastic T cells as well. Coexpression of CD3 and CD20 was also demonstrated on these large cells in some of these cases (number not specified).…”
Section: Aberrant Antigen Expressionmentioning
confidence: 94%
“…116 This dual genotype occurs either because of lineage infidelity (a single clone of cells exhibiting both rearrangements) or occurrence of 2 distinct clones in the same lymphoma (first, phenotypically neoplastic cells of particular lineage and second, an oligo or monoclonal clone of reactive cells of other lineage) 116,129 (Table 5). 132 1 PTL-U CD20 Absent Oshima et al 140 1 PTL-U CD20 Absent Balmer et al 141 1 PTL-U CD20 Absent Lee et al 108 1 PTL-U CD20, CD79a Neck lymph node involvement Martin et al 114 1 PTL-U CD20 Absent Martin et al 114 1 MF CD20 Absent Sen et al 115 1 MF CD20 Inguinal lymph node involvement Rahemtullah et al 106 2 MF CD20 Absent Garcia-Herrera et al 25 1 Despite a high prevalence of 50% (2 of 4) 116 and 20% (4 of 13) 130 of dual genotypes in Sezary syndrome found in 2 studies, very few cases of bigenotypic cutaneous lymphomas have been cited in literature. In a large series by Kazakov et al, 129 the dual genotype was seen in only 1% of primary cutaneous lymphomas.…”
Section: Gene Rearrangement Studiesmentioning
confidence: 96%
See 2 more Smart Citations